Reflections upon immunological mechanisms involved in fertility, pregnancy and parasite infections. (November 2019) - Persson, Gry; Ekmann, Josephine Roth; Hviid, Thomas Vauvert F.
Highlights: Modulation of the immune system is important for reproduction and fertility. Host immune regulation by helminthic parasites may influence female fecundity. The review focuses on mechanisms affecting fertility in women infected with helminths. Research in parasitic interactions may help unlock immune mechanisms in fertility. Abstract: During a pregnancy, the mother accepts her semi-allogeneic fetus with no signs of immunological rejection. Therefore, some modulation of the maternal immune system must occur. Similarly, changes in the host's immune system occurs during infections with parasites. In a study conducted in an endemic area in Bolivia, it has been reported that women infected with either the helminthic parasite roundworm or hookworm were estimated to give birth to either two more, or three fewer, children than uninfected, endemic women, respectively. Immune regulation by helminthic parasites is a rather well-researched concept, but there are few reports on the effects on human fecundity. The current review focuses on mechanisms of possible importance for especially the increased fertility rates in women infected with roundworm. The host immune response to roundworm has been hypothesized to be more favourable for a successful pregnancy because it bears resemblance to the anti-inflammatory immunological responses observed in pregnancy, steering the immunological response away from a pro-inflammatory state that seem to suppress fecundity. Further research into parasitic worm interactions, fertility, and the molecular mechanisms that they unfold may widen our understanding of the immunomodulatory pathways in both helminthic infections and in fertility and pregnancy.